Science Without God? Rethinking the History of Scientific Naturalism, edited by Peter Harrison and Jon H. Roberts - Dumsday, Travis (Religious Studies and Theology, 2020)
Science Without God? Rethinking the History of Scientific Naturalism, edited by Peter Harrison and Jon H. Roberts. Oxford University Press, 2019. xv + 263 pp. 99 ISBN: 978-0-19-883458-8